NEW INFORMATION AND COMMUNICATION TECHNOLOGIES (NTICS) IN EDUCATION: THE IMPORTANCE OF DIGITAL LITERACY - Nunes Sapori, Aline (Revista Gênero e Interdisciplinaridade, 2023)
This article is the result of studies and research on the new information and communication technologies in education, the contribution and importance of digital literacy. It aims to open a discussion around digital literacy, in order to understand it better, and also to think about the different ways to incorporate the modalities of literacy into educational practices. The hypothesis that guides this investigation is that teachers do not yet have autonomy in the use of New Information and Communication Technologies (ICTs). This work disposed of the methodology the investigation on the bibliographic research, with basic strategic intention, descriptive objective, within a qualitative perspective when applying the hypothetical-deductive method. It is observed that there is still a lot of resistance of the teacher to develop active methodologies, mainly through remote teaching, with the emergence of the Coronavirus – COVID19 pandemic and the modifications related to teaching, numerous articles have been published, exposing the difficulties that people, although literate, suffer in the use of new technologies. The plans that began to be taught in virtual environments, have numerous resources to be used, allowing a greater diversity in the presentation of the programmatic content. Even so, access to such infrastructures provided through technologies becomes limited when both the teacher and the student do not have mastery of such tools.